MXene interlayered crosslinked conducting polymer film for highly specific absorption and electromagnetic interference shielding. Issue 2 (12th May 2020) - Bora, Pritom J.; Anil, Amith G.; Ramamurthy, Praveen C.; Tan, Daniel Q.
Abstract : In this work, the electromagnetic interference (EMI) shielding properties of an MXene interlayered crosslinked conducting poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) polymer film are investigated. Abstract : In this work, the electromagnetic interference (EMI) shielding properties of an MXene interlayered crosslinked conducting poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) polymer film are investigated. The introduction of a crosslinker into PEDOT:PSS makes PEDOT:PSS water insoluble. An average EMI shielding effectiveness (SE) of ∼41 dB (corresponding to 99.999% blockage) was obtained for a solution coated 6 ± 0.2 μm thick optimized crosslinked PEDOT:PSS-Ti3 C2 T x MXene (XPM50) nanocomposite film. Electrodynamic modelling and simulation also suggest an excellent SE for this nanocomposite system. From an application point of view, the specific EMI SE (SSE)/thickness ( t ) or absolute EMI SE is the most useful factor. The absolute EMI SE of the XPM50 film is observed to be 89 924 dB cm 2 g −1, which is nearly nine times higher than that of the pristine PEDOT:PSS film and more than three times higher than that of the Ti3 C2 T x MXene film. Mechanistically, the superior EMI shielding due to absorption (SEA ) is intrinsically predominant. The crosslinked PEDOT:PSS interconnects with the Ti3 C2 T x MXene flakes, generating more absorption sites and enhanced electrical conductivity which is responsible for the high SEA value. The XPM50 film also fulfils many commercial requirements, especially solution processability and outstanding absolute EMI SE, which makes it an attractive EMI shield for real time applications such as telecommunications, health care systems, detective systems, defence, and aerospace applications.